2021
DOI: 10.1080/21655979.2021.2009959
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of HPV 16/18 genotyping and geminin mRNA quantification in low-grade cervical squamous intraepithelial lesion

Abstract: Low-grade cervical squamous intraepithelial lesion is a precancerous neoplasia that has appreciable probability to evolve into malignancy. To explore the prognostic value of HPV 16/18 genotyping and geminin mRNA quantification in predicting the progressiveness of LSIL. We recruited 212 participants who were negative for intraepithelial lesion or malignancy (NILM 76), low-grade squamous intraepithelial lesion (LSIL 85), high-grade squamous intraepithelial lesion (HSIL 36) and cervical intraepithelial neoplasia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…However, more women with CIN3 or CC had geminin positivity staining as compared to those with CIN1 or CIN2 (Table 2 ), and the correlation was significantly higher for CC compared to CIN1 or CIN2 (Table 3 ). Zheng et al [ 16 ] also found HPV 16/18 positivity status, expression of geminin, presence of squamocolumnar junction, and size of lesion as independent predictors for differentiating between low-grade squamous intraepithelial lesions and high-grade squamous intraepithelial lesions. They reported HPV 16/18 status and geminin as the most significant associations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more women with CIN3 or CC had geminin positivity staining as compared to those with CIN1 or CIN2 (Table 2 ), and the correlation was significantly higher for CC compared to CIN1 or CIN2 (Table 3 ). Zheng et al [ 16 ] also found HPV 16/18 positivity status, expression of geminin, presence of squamocolumnar junction, and size of lesion as independent predictors for differentiating between low-grade squamous intraepithelial lesions and high-grade squamous intraepithelial lesions. They reported HPV 16/18 status and geminin as the most significant associations.…”
Section: Discussionmentioning
confidence: 99%
“…They reported a sensitivity of 95%, a positive predictive value of 85.7%, and an accuracy of 88.2%. Geminin levels were found to increase with the grade of the lesion and also change during the progression of LSIL/CIN1 to HSIL/CIN2-3 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…HR-HPV is an indispensable precursor of CC, whereas LR-HPV is integral for genital mucosal warts. In particular, HR-HPV 16/18 or non-16/18 HR-HPV are considered oncogenic and causative [4][5][6]. Although occasionally eliminated by immune processes, HR-HPV is now progressively difficult to eliminate due to the influence of smoking, alcohol consumption or irregular sexual activity.…”
Section: Introductionmentioning
confidence: 99%